2016
DOI: 10.1136/esmoopen-2016-000111
|View full text |Cite
|
Sign up to set email alerts
|

Radiological imaging markers predicting clinical outcome in patients with metastatic colorectal carcinoma treated with regorafenib: post hoc analysis of the CORRECT phase III trial (RadioCORRECT study)

Abstract: ObjectiveTo identify imaging markers predicting clinical outcomes to regorafenib in metastatic colorectal carcinoma (mCRC).MethodsThe RadioCORRECT study is a post hoc analysis of a cohort of patients with mCRC treated within the phase III placebo-controlled CORRECT trial of regorafenib. Baseline and week 8 contrast-enhanced CT were used to assess response by RECIST 1.1, changes in the sum of target lesion diameters (ΔSTL), lung metastases cavitation and liver metastases density. Primary and secondary objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
0
24
0
4
Order By: Relevance
“…Recently, a retrospective analysis of patients having undergone treatment with regorafenib showed that the radiologic occurrence of cavitation to lung metastasis is associated with favorable outcome [26].…”
Section: Regorafenibmentioning
confidence: 99%
“…Recently, a retrospective analysis of patients having undergone treatment with regorafenib showed that the radiologic occurrence of cavitation to lung metastasis is associated with favorable outcome [26].…”
Section: Regorafenibmentioning
confidence: 99%
“…As aforementioned, TTP in RESORCE did not differ between RECIST v1.1 and mRECIST, highlighting the need to develop better tools to capture treatment benefit. However, recent studies suggest that imaging techniques may predict response to regorafenib, and this represents an area of active research [107,[115][116][117]. Some studies have shown that small changes in tumor density and size or early cavitation of lung metastases could predict response to regorafenib [115][116][117].…”
Section: Predictive Markers Of Regorafenib Activitymentioning
confidence: 99%
“…However, recent studies suggest that imaging techniques may predict response to regorafenib, and this represents an area of active research [107,[115][116][117]. Some studies have shown that small changes in tumor density and size or early cavitation of lung metastases could predict response to regorafenib [115][116][117]. A post hoc analysis of CORRECT (RadioCORRECT) showed that cavitation in pulmonary metastases, seen with contrast-enhanced computed tomography, was associated with absence of progression at Week 8 in regorafenib-treated patients with mCRC [117].…”
Section: Predictive Markers Of Regorafenib Activitymentioning
confidence: 99%
“…Changes such as density reduction in lung metastases, lung metastases cavitation, and longer time from first diagnosis to metastatic disease have been associated with favorable responses to regorafenib in clinical studies. 37,80,81 Such events may encourage clinicians and patients to persist with therapy, using dose adjustments to manage toxicities when necessary. 14,19,23,[82][83][84][85][86][87] However, more evidence is required to determine whether such clinical responses could be used as robust markers that inform clinical decisions.…”
Section: Clinical Markers Of Responsementioning
confidence: 99%